2022
DOI: 10.1249/01.mss.0000877732.42096.e6
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activity And User-perceived Exertion During Immersive Virtual Reality Exergaming Incorporating Adaptive Cable Resistance

Abstract: 217cases, aerobic--training is poorly tolerated. Thankfully, other modes of exercise training, such as resistance training (RT) have previously been successfully integrated into general rehabilitation programs. However, it is not known whether such exercise modalities are sufficient to enhance cardiopulmonary system function and whether they could be utilized in rehabilitation programs that integrate interventions related to respiration. PURPOSE: To determine the effect of different RT modalities on chest expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Consequently, VR technology is increasingly being used in various areas of life and science, including health care, rehabilitation, psychology, education, engineering, manufacturing, and entertainment [2,[4][5][6][7][8][9][10]. The development of information technology and the ever-increasing popularity of video games are often associated with the reduction of a person's physical activity (PA) in favor of prolonged sitting in front of a computer, resulting in poor well-being and progressive deterioration in the physical and mental health status [11][12][13][14] Therefore, in recent years, there has been a growing interest in active virtual reality games (AVRGs), which provide entertainment and encourage PA [15][16][17][18][19][20][21][22][23][24][25]. AVRGs are video games that require users to perform physical exercise [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, VR technology is increasingly being used in various areas of life and science, including health care, rehabilitation, psychology, education, engineering, manufacturing, and entertainment [2,[4][5][6][7][8][9][10]. The development of information technology and the ever-increasing popularity of video games are often associated with the reduction of a person's physical activity (PA) in favor of prolonged sitting in front of a computer, resulting in poor well-being and progressive deterioration in the physical and mental health status [11][12][13][14] Therefore, in recent years, there has been a growing interest in active virtual reality games (AVRGs), which provide entertainment and encourage PA [15][16][17][18][19][20][21][22][23][24][25]. AVRGs are video games that require users to perform physical exercise [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, published research findings are inconclusive. Some researchers point to moderate to high levels of exercise intensity in those playing AVRGs, especially when using exercise machines (eg, cycle ergometers, treadmill) [ 16 , 18 , 19 , 22 , 23 ]. Locomotion has been shown to promote exercise intensity and enhance the immersion experience.…”
Section: Introductionmentioning
confidence: 99%
“…The health-promoting nature of exercise during immersive virtual reality video gaming (AVRGs) has also been documented by other authors [ 2 – 5 , 10 ]. However, the studies refer to able-bodied users without fitness deficits.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, the player's performance and feelings of autonomy also contributed to enjoyment of the game. taken together, practitioners could opt to use high intensity in the game to induce higher HR response without significant changes in the affect/pleasure, which could induce improvements in physical fitness with pleasure, which might increase adherence [17].…”
Section: Resultsmentioning
confidence: 99%
“…the possible interference of psychological variables (entertainment, pleasure) on the physiological response to exercise is identified in several studies. A recent investigation assessed an immersive virtual reality (iVR) device that integrated cable resistance training and not only found a substantial metabolic demand which meets the ACSM vigorous exercise requirements, but also high ratings of enjoyment that seemed to distract users from perceived exertion [17]. Gomez, Browne, Almalouhi et al [17] found results which suggest similar muscle activation responses compared to traditional resistance exercises, as demonstrated by prior evidence, and reinforce the ability of an iVR exergaming system to make practitioners exercise at a high intensity while distracting them from the high demands of the exertion.…”
Section: Introductionmentioning
confidence: 99%